Kedudukan Guru sebagai Pendidik Menurut Pandangan Islam - Taufik, Taufik; Faliani, Eli; Ulya, Hanum Kholidiya; Sari, Nurul Vita (Universitas PGRI Semarang, 2024)
The knowledge and skills acquired by teachers are knowledge related to the development of professional tasks, as well as social and humanitarian work. In the National Education System law, Article 27 paragraph 3 stipulates three roles of teachers, namely: 1) As a teacher, 2) as a guide, 3) As a class administrator; Communicate the role and position of the teacher in a prophetic treatise for humanity, basically carrying out the mission of Rahmatan li al 'alamin, which is a mission to call on humans to submit and worship Allah SWT.